Review On Siddha Drugs Containing Coconut In The Treatment Of Gunma Rogam - Thayalini, T.; Lakshinevetha, G.; Vidhya, M. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2015)
The Gunma Rogam is described under the Uthararogam in "Pararajasegaram". It is caused by a person's habit and mental make up. The person's habit stated that excessive consumption of astringent food, intake of yams and spices, unhealthy food habits especially not adhering to a proper time schedule and emotional imbalance anger, fear, anxiety, etc.. Among Eight types of Gunmam, the clinical features of valiGunmam are compared with the clinical features of Peptic ulcer. In previous study, it had been stated that virgin coconut oil has the antimicrobial property and it kills H. pylori, one of the causative organism of stomach ulcer. Many Siddha drugs are mentioned in the treatment of Gunma rogam. Aim of the study was to review the drugs containing coconut in the treatment of Gunmam.. Data of drugs containing coconut has been collected with amount and anupanam from five different Siddha text books. Information were collected from Jaffna Public library and Library of Unit of Siddha Medicine. Five drugs were identified from 5 literatures which are containing coconut as one of the ingredients in the treatment of Gunmarogam. Coconut milk is used in thengai pal ennai. thengaikulambu&sharathailam. In thengaisharamand in thengaikaduku, whole coconut is being in use. Induppu is also one of the ingredient in four of the reviewed medicine. In ancient time. our ancestors have used medicines prepared with coconut for Gunmamsince it could have the property to inhibit H. pylori. Along with this, salt also neutralizes the acid and cures Gunmam. In future lab study on drugs containing coconut should be carried out in order to find the action of these drugs.
Keywords: Gunma rogam; Drugs containing coconut; Treatment